Observation of tool use in striped skunks: how community science and social media help document rare natural phenomena. Issue 11 (15th November 2018) - Pesendorfer, Mario B.; Dickerson, Suzanne; Dragoo, Jerry W.
Abstract: Tool use, the manipulation of one object to change the state of another, is found in <1% of animal taxa and most often observed in captivity. Here, we report the observation of tentative tool use in a wild striped skunk ( Mephitis mephitis ), captured by a trail camera in the front yard of a hobby naturalist who shared the photographs on social media. The skunk is shown manipulating a rock in a manner that strongly suggests the goal of breaking the frozen surface of a water bowl to drink. Skunks join other carnivores that innovated tool use and proto‐tool use in the context of extractive foraging. Their versatile dexterity and manipulative foraging, likely facilitated by their large relative brain size, provide the ideal context for the innovation of novel foraging techniques. We therefore hypothesize that tool use will be observed in other members of the skunk family (Mephitidae), particularly as the broad availability of trail cameras, and the rapid dissemination of interesting observations via social media will increase the discovery rate of rare natural history phenomena. We encourage our colleagues to strengthen this pipeline to discovery, which reverses the information flow of community science projects, to bring amateur and professional naturalists closer together.